EDUKASI IMPLEMENTASI KEBIJAKAN MUTU BAGI PETUGAS SISTEM INFORMASI MANAJEMEN DAN PENGELOLAAN ADMINISTRASI TERINTEGRASI DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Fithri Handayani Lubis; Rizka Annisa; Diana Sinulingga; Elisabeth Dame Manalu (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Hospital information systems have an important role in clinical and administrative services. Hospitals need a management information system (MIS) and hospital administration management to improve the quality of medical services. Hospital MIS (SIMRS) and integrated hospital administration management are designed to integrate the main hospital functions into one unified system that is stored in a central database. Regulation of the Minister of Health of the Republic of Indonesia Number 82 of 2013 Article 3 states that every hospital is obliged to implement a Hospital Management Information System (SIMRS). In Permenkes No. 30 of 2019 concerning electronically integrated business licensing or online single submission, hereinafter abbreviated as OSS, is a business license issued by the OSS institution for and on behalf of the minister, governor, or regent/mayor to hospital owners and managers through an integrated electronic system. The government is targeting all hospitals in Indonesia to have SIMRS which is integrated in the management of hospital administration. Hospitals that do not carry out SIMRS and good administrative management will affect the quality of service at the hospital, including causing human errors and mismanagement in recording health data, waiting time for services to be longer which can lead to accumulation of patients. The implementation of SIMRS and good and correct administrative management will have a positive impact on management, increase efficiency, and facilitate decision making in the future.